SANCTIONS: POLITICAL AND ECONOMIC FORESHORTENING - I. D. Matskulyak; G. N. Bogacheva; B. A. Denisov (Вестник университета)
A number of aspects of the change of the political and economic relations, apparent by the sanctions policy of the western states to the Russian Federation and its realization, has been considered. The balance between the liberty, equality and fraternity, the perfect competition and free business, on the one hand, and the competition of smothering, ball and chain, on the other hand, – has been disclosed. It has been substantiated, that the western states seek to substitute the colonial influence in the past for sanctions pressure in our days. It allows them to get not only the competitive advantage, but also to obtain the absolute dictatorship sometimes. The conclusion has been made, that external intervention in the natural course of managing and especially the rough administrative influence never gives a positive effect.